2006
DOI: 10.1021/jp065000l
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Structural Behavior of Indirect NMR Spin−Spin Couplings in the Backbone of Nucleic Acids

Abstract: Calculated indirect NMR spin-spin coupling constants (J-couplings) between (31)P, (13)C, and (1)H nuclei were related to the backbone torsion angles of nucleic acids (NAs), and it was shown that J-couplings can facilitate accurate and reliable structural interpretation of NMR measurements and help to discriminate between their distinct conformational classes. A proposed stepwise procedure suggests assignment of the J-couplings to torsion angles from the sugar part to the phosphodiester link. Some J-couplings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…High‐level ab initio calculations with gauge‐independent atomic orbitals (GIAO) have been shown to provide good agreement with the experimental NMR data 32, 33. The combination of theoretical calculations and experimental NMR spectra has already been used for the solution of various stereochemical problems 34–36…”
Section: Introductionmentioning
confidence: 94%
“…High‐level ab initio calculations with gauge‐independent atomic orbitals (GIAO) have been shown to provide good agreement with the experimental NMR data 32, 33. The combination of theoretical calculations and experimental NMR spectra has already been used for the solution of various stereochemical problems 34–36…”
Section: Introductionmentioning
confidence: 94%
“…A different hypothetical explanation could lie in the process of interpretation of the NMR experimental data. Their relative scarcity caused by the low density of protons, and sometimes equivocal interpretation of experiments such as indirect spin−spin couplings (“J-couplings”) may cause uncertainties especially in the assignment of torsions α and ζ of the phosphodiester linkage [116]. The resulting DNA structure may then be influenced by the refinement protocol in which the experimental restrains are combined with force fields in a computer simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Structural interpretation of the 2 J P,C3′ and 2 J P,C5′ couplings proposed by the authors were only qualitative, namely, because the two‐dimensional character of their dependencies implied that similar 2 J PC values could correspond to different phosphate conformers. Nevertheless, it was unequivocally found that the 2 J P,C3′ and 2 J P,C5′ couplings could be definitely assigned to the nucleic acid backbone torsion angles, ζ and α, respectively.…”
Section: Computation Of Spin–spin Coupling Constants Involving Phosphmentioning
confidence: 90%
“…As an example of the biochemical applications of computational spin–spin coupling constants involving phosphorous, Sychrovský et al performed B3LYP/IGLO‐II (III) calculations of n J PH and n J PC ( n = 2, 3, 4) in the model fragments across the P‐O···H‐C linkage between the nucleic acid backbone phosphate and the nucleic acid base used for the structure determination of nucleic acids. It was shown that 3 J PC and 3 J PH demonstrated a pronounced Karplus‐type dihedral angle dependence, as illustrated in Figure for the model complex of guanine base interacting with dimethyl‐phosphate (G···dmP) 9, as shown in Scheme .…”
Section: Computation Of Spin–spin Coupling Constants Involving Phosphmentioning
confidence: 93%